GERAKAN ANTI PERUNDUNGAN: TINJAUAN FILSAFAT BIMBINGAN KONSELING - Muhammad Akmal Yazdy Ihsany; M. Haddadalwi Nasyafiallah; Najlatun Naqiyah (UIN Sunan Kalijaga Yogyakarta, 2023)
This research aims to determine the philosophical basis by examining the ontological, epistemological and axiological aspects of the Anti-Bullying Movement (GAP). Through a literature study reinforced with field data from interviews, observations and documentation, this research concludes that GAP is essentially an effort to prevent and deal with bullying in schools as a follow-up to government policy as well as an initiative by schools to make educational units free from bullying, both directly or online. Meanwhile, epistemologically, in order to seek knowledge about GAP at MA Bahauddin, a survey stage was used, including interviews, selecting change agents, training change agents, anti-bullying campaigns and evaluation. The axiological aspect can be seen in the value and usefulness of the GAP program at MA Bahauddin. GAP has value for schools, teaching staff and students. Namely increasing the role and professionalism of guidance and counseling teachers, providing an understanding of bullying and efforts to prevent and handle it and increase awareness regarding bullying. Keywords: Anti-bullying movement, Madrasah Aliyah, Ontology, Epistemology, Axiology